Politics of Neopatrimonialism and the Dynamics of Nationalisation Policy in the “Socialist Tanzania” - Elias, Stanley (Indonesian Journal of Political Studies, 2025)
This study examines the dynamics of nationalization policy in Tanzania during the early post-independence years using a theory of neopatrimonialism. Building on Bratton and van de Walle’s identification of presidentialism, clientelism, and the particularistic use of state resources as hallmarks of neo-patrimonial governance, this study explores how these characteristics shaped the industrial policy during the “socialist Tanzania”. By focusing on the period between 1967 and 1985, the study traces the early industry boom from 1961 to 1968 and the subsequent de-industrialization period. I argue that the concentration of power in the presidency of Julius Nyerere and his State Party resulted in inefficiencies within the nationalized industrial sector. The study highlights that the nationalization policy produced an oversized, poorly adapted industrial base that failed to align with Tanzania’s resource and skills environment. Ultimately, this governance structure contributed to the crisis of the 1970s. The findings suggest that while nationalization initially promised rapid industrial transformation, it was undermined by neopatrimonial tendencies, prompting a later shift to market-oriented reforms. The study contributes to broader debates on state-building, industrial policy, and the legacies of postcolonial governance in Africa.